Analisis Teknologi QR Code dalam Pembelajaran Matematika di Sekolah Dasar (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the use of technology, especially QR Code, in mathematics learning in elementary schools. Using a literature review method, data was collected from various relevant national and international journals. The results of the study indicate that the integration of QR Code in mathematics learning has proven effective in improving student learning outcomes, interest, and engagement. QR Code is used in various forms of media, such as Student Worksheets (LKS), comics, flash cards, posters, and interactive videos, which support contextual, visual, and independent learning. The application of QR Code also helps students understand abstract concepts, improves numeracy and spatial skills, and supports the development of 21st century skills. This study concludes that the use of QR Code is an innovative strategy and is feasible to be applied in mathematics learning at the elementary school level.